Posted by
**unknown** on
.

could you walk-through the steps to solving this problem because I am stuck;

3x-5(3x-7)=2(x+9)+45

Let me know if you have a question in any step.

3x-5(3x-7)=2(x+9)+45

3x-15x+35= 2x+18+45

-12x+35 = 2x+63

-35 -35

-12x= 2x +63-35

-12x= 2x +28

-2x -2x

-12x-2x = 28

-14x= 28

-14x/-14= 28/-14

x = -2

to check just substitute the answer for x to ever x in the original problem.

3x-5(3x-7)=2(x+9)+45

3(-2)-5(3(-2)-7)=2(-2+9)+45

-6 -5 (-6-7)= 2(7)+45

-6-5(-13)=14+45

-6+65=59

59=59 it checks.

You really helped me out. I know see how to work out other problems like this one. Thank you very much!!!